TEOREMA PALEY-WIENER-SCHWARTZ PADA DOMAIN NON KONVEKS - , CYNTHIA TRI OCTAVIANTI, Dr. Ch. Rini Indrati, M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Paley-Wiener theorem is a theorem related to the Fourier transforms of analytic functions having continuous partial derivatives up to infinite times. The theorem has been generalized to be Paley-Wiener-Schwartzs theorem by characterizing Schwartz test functions and distributions with compact support. Usually Paley-Wiener-Schwartz theorem works on the domain that is compact and convex. In this thesis we discuss the theorem of Paley-Wiener- Schwartz on compact sets. Further we discuss Paley-Wiener-Schwartz theorem generated by the sequences of numbers and polynomials which can be nonconvex. Also we discuss the theorem of Paley-Wiener-Schwartz generated by the set of convex-d.